The IMPROVING THE ABILTY OF READING QUR’AN USING THE IQRA METHOD IN SDN 262 PANYILEUKAN BANDUNG - Ruslandi, Ruslandi (EDUKASI: Jurnal Pendidikan Islam, 2019)
This article discusses the problems in reading the Koran which are good and right in accordance with the rules of Al-Qur'an reading, which indeed not a few high school elementary students in terms of the ability to read it is still very low. The correct Qur'an reading rules are measured from the level of fluency, Makhorijul letters, Tajweed, Tartil, Understanding and Kefashihan. However, in the study found in the field whose value was lowest when measured, namely in terms of reading with Tartil, the author reacted to it by using the Al-Qur'an reading method which was quite popular in learning using the Iqra method. The purpose of this study is to find out how the application of the Iqra method in improving the ability to read the Qur'an. Tujuan dari penelitian ini yakni untuk mengetahui bagaimana penerapan metode Iqra dalam meningkatkan kemampuan membaca Al-Qur’an.